OPTIMIZATION OF THE METHOD FOR OBTAINING NANOCAPSULES, DEVELOPMENT OF THE METHODS OF DETERMINING THE DEGREE OF CINNARIZINE INCLUSION IN A PROLONGED DOSAGE FORM BASED ON POLY-D, L-LACTID-CO-GLICOLIDE, AND ITS VALIDATION - M. V. Sorokoumova; N. V. Blagorazumnaya; V. A. Kompantsev; L. I. Shcherbakova; N. S. Zyablitseva; Yu. G. Medvetskaya; T. M. Vasina; K. A. Miroshnichenko (Фармация и фармакология (Пятигорск), 2019)
Common pathologies of the cardiovascular system are cerebrovascular disorders, for which cinnarizine is prescribed. An innovative, prolonged nanocapsule dosage form based on poly-D, L-lactide-co-glycolide (PLGA) has been developed.The aim of the research was improvement of the technology and development of the methods for determining the level of cinnarizine inclusion in nanocapsules. The research problem consisted of a great number of drug encapsulation peculiarities, as well as various physicochemical properties of the substances that cannot be taken into account in the existing methods of determination.Materials and methods. In the study, the following substances were used: cinnarizine, PLGA (50:50), polyvinyl alcohol (PVA). The remaining reagents and solvents fitted into the category of chemically pure. For development of the methods for quantitative determination of cinnarizine and its validation, a spectrophotometric method of analysis was used. Model mixtures used as objects of the study, had been prepared. Validation assessment of the methods was carried out upon such indicators as specificity, linearity, detection limit, repeatability, reproducibility.Results. Methods for spectrophotometric determination of the degree of cinnarizine inclusion has been developed. It has been established that encapsulation reaches 63.74%. Validation testing methods has been carried out. The results of such tests as specificity, linearity, detection limit, repeatability, reproducibility correspond to the safe range of values regulated by Product specification file. Due to the impossibility of determining the degree of cinnarizine inclusion on the basis of standard methods of preparation, the technology of producing nanocapsules has been adjusted.Conclusion. The technology has been optimized and new techniques have been developed. Taking into account the characteristics of production and the physicochemical properties of the components, they make a reliable analysis of the degree of cinnarizine inclusion in nanocapsules possible. The relative error of the developed methods of determination does not exceed ± 2.67%. Based on the results of the validation assessment, this methods is valid for all indicators.